Destruction of bacterial biofilms by polymorphonuclear neutrophils: relative contribution of phagocytosis, DNA release, and degranulation - Meyle, Eva; Stroh, Petra; Günther, Frank; Hoppe-Tichy, Torsten; Wagner, Christof; Hänsch, Gertrud Maria (The international journal of artificial organs, 2010)
Bacteria organized in biofilms are a common cause of relapsing or persistent infections, and the ultimate cause of implant-associated osteomyelitis. In these patients, biofilms of staphylococci are prevalent. Bacteria organized as biofilms are relatively resistant towards antibiotics and biocides, and it is also assumed that they may escape host defense mechanisms. In this context, we have studied how polymorphonuclear neutrophils (PMN), the ?first line of defense? against bacterial infection, interact with biofilms generated in vitro. We found that PMN recognize biofilms and activate defense-associated reactions, including phagocytosis, degranulation of lactoferrin and elastase, and DNA release as well. Destruction of biofilms ensues, showing that biofilms are not inherently protected against the attack by phagocytic cells.